IMPLEMENTING CLASSROOM AGREEMENTS TO FOSTER TOLERANCE AND REDUCE BULLYING - Viona Dwi Puspitasari; Kurniana Bektiningsih (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
This study was motivated by the prevalence of verbal and social bullying in elementary schools, which is closely linked to low tolerance among Grade V students at SD Negeri Sukorejo 01, Sutojayan District, Blitar Regency. The background of this research is the persistence of verbal and social bullying in elementary schools, which is closely associated with low levels of tolerance among students. The study aims to analyze: (1) the implementation of tolerance habituation through classroom agreements, (2) forms of bullying behavior that emerge in the classroom, and (3) teachers’ perceptions of the role of classroom agreements in fostering tolerance and minimizing bullying. This research employed a qualitative descriptive approach. Data were collected through classroom observations, in-depth interviews with teachers and the school principal, and documentation. The findings indicate that classroom agreements developed through a participatory process between teachers and students function not only as behavioral guidelines but also as an effective medium for internalizing values of tolerance, such as mutual respect, appreciation of differences, and polite interaction. Bullying behaviors identified were predominantly verbal and social in nature. Teachers perceived classroom agreements as significantly contributing to the development of students’ tolerance and to the reduction of bullying, provided that they are supported by teacher role modeling, consistent implementation, and ongoing guidance. Overall, classroom agreements have been shown to be an effective strategy for creating a safe, inclusive, and conducive learning environment.